2020
DOI: 10.1002/cssc.202002137
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal and Nitrogen Co‐Doped Carbon‐based Electrocatalysts for the Oxygen Reduction Reaction: From Active Site Insights to the Rational Design of Precursors and Structures

Abstract: Considering the urgent requirement for clean and sustainable energy, fuel cells and metal‐air batteries have emerged as promising energy storage and conversion devices to alleviate the worldwide energy challenges. The key step in accelerating the sluggish oxygen reduction reaction (ORR) kinetics at the cathode is to develop cost‐effective and high‐efficiency non‐precious metal catalysts, which can be used to replace expensive Pt‐based catalysts. Recently, the transition metal and nitrogen co‐doped carbon (M−Nx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 203 publications
0
25
0
Order By: Relevance
“…The E onset and E 1/2 values for other catalysts are slightly lower (Table 3). In general, the good ORR activity of prepared catalysts can be linked with the micro‐mesoporous nature and the presence of M‐N x centres and N‐pyridinic moieties in the catalysts as confirmed by the XPS and N 2 physisorption analysis [29,63,64] . Linear sweep voltammetry curves at different rotation rates and the corresponding Koutecky‐Levich (K−L) plots for O 2 reduction on the prepared catalysts are shown in Figures S4 and S5, respectively.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The E onset and E 1/2 values for other catalysts are slightly lower (Table 3). In general, the good ORR activity of prepared catalysts can be linked with the micro‐mesoporous nature and the presence of M‐N x centres and N‐pyridinic moieties in the catalysts as confirmed by the XPS and N 2 physisorption analysis [29,63,64] . Linear sweep voltammetry curves at different rotation rates and the corresponding Koutecky‐Levich (K−L) plots for O 2 reduction on the prepared catalysts are shown in Figures S4 and S5, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…In general, the good ORR activity of prepared catalysts can be linked with the micro-mesoporous nature and the presence of M-N x centres and N-pyridinic moieties in the catalysts as confirmed by the XPS and N 2 physisorption analysis. [29,63,64] Linear sweep voltam- Table 3. Electrochemical results of as-synthesised catalysts and comparison with other catalysts found in the literature.…”
Section: Electrochemical Characterisation Of the Electrocatalystsmentioning
confidence: 99%
“…Under the alkaline conditions of these studies, two reduction pathways are commonly considered to be possible 17…”
Section: Main Textmentioning
confidence: 99%
“…Under the alkaline conditions of these studies, two reduction pathways are commonly considered to be possible 17 : 1b presents current versus voltage plots for electrodes that are coated with a SAM of achiral 3-mercaptopropionic acid (blue) or with chiral L-cysteine (red). The significant difference of current density in O2 and N2 saturated solutions indicates that both chiral-and achiral-functionalized electrodes show activity for oxygen reduction.…”
Section: Main Textmentioning
confidence: 99%
“…Fe or Co) to obtain optimal electronic and geometric structures. [14][15][16][17][18][19][20][21] More concretely, density functional theory (DFT) calculations suggested that co-doping of Fe and N in the form of possible FeN 4 sites on a graphitic substrate could be as active as Pt for O 2 adsorption and subsequent O]O bond breaking during the ORR. [22][23][24][25] In this sense, nitrogen-containing functional groups on a graphitic matrix also play a fundamental role in the performance and electronic conductivity of electrocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%